2014
DOI: 10.5897/ajb2013.12496
|View full text |Cite
|
Sign up to set email alerts
|

Determination of ploidy among Yam (Dioscorea spp.) landraces in Kenya by flow cytometry

Abstract: Yam (Dioscorea spp.), a traditional crop in Kenya has not undergone improvement and little has been done to understand its genetic background. The taxonomy and phylogeny of the local landraces has not been fully studied. The main cultivated species is Dioscorea minutiflora Engl. Others found with low distribution are Dioscorea alata L., Dioscorea bulbifera L. and Dioscorea odoratissima Pax. Flow cytometry was used to estimate the ploidy level of 155 accessions of Kenyan yam including two checks, TDr.18544 a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
3
1
Order By: Relevance
“…The ploidy levels include diploid (D. dumetorum), tetraploid (D. cayenensis, D. rotundataand D. alata), hexaploids (D. alata and D. rotundata) and octoploids (D. cayenensis) (Ngo-Ngwe et al, 2014). Contrary to previous reports of triploids, pentaploids or octoploids among D. alata collections from Chad, Puerto (Muthamia et al, 2014) and IITA Ibadan (Obidiegwu et al, 2009b); Cameroon accessions lack these ploidy levels. Furthermore, only diploids have been reported among D. dumetorum collection in Cameroon (Ngo-Ngwe et al, 2014), yet Obidiegwu et al (2009a), reported the existence of triploids in IITA collection.…”
Section: Genetic Diversity Of Yams In Camerooncontrasting
confidence: 99%
“…The ploidy levels include diploid (D. dumetorum), tetraploid (D. cayenensis, D. rotundataand D. alata), hexaploids (D. alata and D. rotundata) and octoploids (D. cayenensis) (Ngo-Ngwe et al, 2014). Contrary to previous reports of triploids, pentaploids or octoploids among D. alata collections from Chad, Puerto (Muthamia et al, 2014) and IITA Ibadan (Obidiegwu et al, 2009b); Cameroon accessions lack these ploidy levels. Furthermore, only diploids have been reported among D. dumetorum collection in Cameroon (Ngo-Ngwe et al, 2014), yet Obidiegwu et al (2009a), reported the existence of triploids in IITA collection.…”
Section: Genetic Diversity Of Yams In Camerooncontrasting
confidence: 99%
“…Ten SSR markers used in this study and the detected 40 alleles are enough to estimate the genetic diversity within the population (Tostain et al 2007, Otoo et al 2015. YM30, Dab2D06, Dab2C05 and Da1A01 were the markers that gave a higher number of alleles in this study, similar to Muthamia et al (2013) and Obidiegwu et al (2009). Dpr3D06 and Dpr3F04 markers gave the lowest number of alleles (2), suggesting their monomorphism, a similar observation to Massawe and Temu (2023).…”
Section: Discussionsupporting
confidence: 78%
“…Microsatellites are also good enough (powerful) to capture genetic diversity information and provide a highlight of genetic resources available in any germplasm. Other researchers also adopted SSR markers to assess the genetic diversity of yam from different geographical regions (Obidiegwu et al 2009, Siqueira et al 2012, Muthamia et al 2013, Arnau et al 2017). This study aimed to assess the morphological and genetic diversity of water yam (D. alata) and the general production constraints of yam in Pwani and Unguja island.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular studies done on Kenyan yams have been minimal. Previous studies have investigated the genetic diversity using polymorphic Simple Sequence Repeats (SSR) markers that distinguished the landraces Muthamia et al (2013) and ploidy levels; this revealed variable ploidy levels among the local yam landraces (Muthamia et al, 2014) and not the phylogeny of the species. Both studies recommended further work on the phylogeny of Kenyan yams.…”
Section: Introductionmentioning
confidence: 99%